Characterization of an ilmenite ore for pressurized chemical looping combustion. (1st February 2016) - Ridha, Firas N.; Duchesne, Marc A.; Lu, Xuao; Lu, Dennis Y.; Filippou, Dimitrios; Hughes, Robin W.
Graphical abstract: Highlights: Characterization results of Canadian ilmenite ore tested in pressurized CLC cycles. Phase diagrams generated to predict phase transformations. Total pressure did not have a noticeable effect on surface morphology. CO partial pressure did not result in significant changes to surface morphology. Larger grains were formed with increasing reaction temperature. Abstract: This work presents the characterization results of a Canadian ilmenite ore tested in pressurized chemical looping combustion cycles. The ilmenite ore was isothermally cycled in a pressurized thermogravimetric analyzer using carbon monoxide as a reducing fuel and air as an oxidizing gas. All samples were calcined prior to submission to cycles. X-ray diffraction (XRD) comparing raw and calcined ore samples indicate the disappearance of ilmenite crystals and the formation of rutile and ferric pseudobrookite. Cycled ilmenite ore surface morphology was found to be insensitive to the total pressure (up to 51 bar) and CO partial pressure (3.2–8.0 bar). These findings are in agreement with thermodynamic equilibrium predictions using FactSage. SEM images reveal the development of cracks in the oxidized particles after 4 redox cycles at 950 °C and 16 bar, which was correlated to the original lamellar structure of the raw ilmenite ore. Increasing the number of redox cycles from 3.5 to 19.5 resulted in large cracks near iron-rich lamellae. Furthermore, the average grain size was smaller after 19.5 cycles. Increasing the reaction temperature from 850 °C to 1050 °C resulted in similar surface morphologies, but increased grain size. Despite being below melting temperatures, the sample cycled at 1050 °C did agglomerate. Local temperature excursions during sample oxidation may have led to melting. This study provides insights into the phase transformations and morphological changes accompanying the use of this type of ilmenite ore in a pressurized chemical looping combustion process, highlighting the need for proper adjustments to the design and operation of the process.